Comparison of Computed and Acquired DWI in the Assessment of Rectal Cancer: Image Quality and Preoperative Staging - Xia, Yihan; Wang, Lan; Wu, Zhiyuan; Tan, Jingwen; Fu, Meng; Fu, Caixia; Pan, Zilai; Zhu, Lan; Yan, Fuhua; Shen, Hailin; Ma, Qianchen; Cai, Gang (Frontiers in Oncology, 2022)
Objective: To evaluate the computed diffusion-weighted images (DWI) in image quality and diagnostic performance of rectal cancer by comparing with the acquired DWI. Methods: A total of 103 consecutive patients with primary rectal cancer were enrolled in this study. All patients underwent two DWI sequences, including conventional acquisition with b = 0 and 1000 sec/mm2 (aDWIb1000) and another with b = 0 and 700 sec/mm2 on a 3.0T MR scanner (MAGNETOM Prisma; Siemens Healthcare, Germany). The images (b=0 and 700 sec/mm2) were used to compute the diffusion images with b value of 1000 sec/mm2 (cDWIb1000). Qualitative and quantitative analysis of both computed and acquired DWI images was performed including signal-to-noise ratio (SNR), contrast-to-noise ratio (CNR), and signal intensity ratio (SIR), as well as diagnostic staging performance. Interclass correlation coefficients, weighted κ coefficient, Friedman test, Wilcoxon paired test, and McNemar or Fisher test were used for repeatability and comparison assessment. Results: Compared with the aDWIb1000 images, the cDWIb1000 ones exhibited significant higher scores of subjective image quality (all P <0.050). SNR, SIR, and CNR of the cDWIb1000 images were superior to those of aDWIb1000 ones (P<0.001). The overall diagnostic accuracy of computed images was higher than that of the aDWIb1000 images in each T stages (P<0.001), with markedly better sensitivity and specificity in distinguishing T1-2 tumors from the T3-4 ones (P<0.050). Conclusion: cDWIb1000 images from lower b values might be a useful alternative option and comparable to the acquired DWI, providing better image quality and diagnostic performance in preoperative rectal cancer staging.